Plantable stem supply system for IITA cassava varieties in Oyo State of Nigeria - Akoroda, M.O.; Oyinlola, A.E.; Gebremeskel, T. (1987)
The overall system for supplying plantable stems of improved cassava varieties from the International Institute of Tropical Agriculture (IITA) was surveyed for Oyo State where IITA is situated. This study examined the relation of spread of adoption of these varieties during the period of 1976 through 1985 to the supply of planting materials. Based on completed questionnaires, reconnaisance visits to 21 of the 24 local government areas of Oyo State, coupled with official documents and personal communications, the team found that: (i) effective distribution of plantable stems to the majority of cassava farmers did not begin until the second half of the 1976–1985 decade, (ii) the required capacity for, and rate of multiplication of IITA cassava varieties was grossly inadequate, (iii) the varieties are yet to be introduced to some localities due to a poor stem supply system for these cassava varieties and (iv) a large potential exists for further adoption of IITA varieties if farmers can obtain more plantable stems. This study identified the short supply of plantable stems to farmers as the chief obstacle to a wider spread, adoption, and use of IITA improved cassava for meeting the food needs of cassava-dependent rural farm families in Oyo State. A greater catalytic role is recommended for IITA to ameliorate the stem supply situation.